Compression behavior and failure mechanisms of concrete masonry prisms - Köksal, HO; Karakoç, C; Yildirim, H (ASCE-AMER SOC CIVIL ENGINEERS, 2005)
To date, only linear elastic analyses have been used to explain the compression behavior of the concrete masonry prisms. In this study, nonlinear three-dimensional finite element analyses, based on both an elastoplastic approach and an isotropic damage model, have been applied to the compression behavior of hollow block and grouted concrete block prisms. Attention is particularly focused on the derivation of material parameters for concrete, grout, and mortar, and also on the improvement of existing code expressions for prism strength. This paper introduce's adequate values for the cohesion and friction angle of,the Drucker-Prager yield criterion and material damage parameters for the damage model for the constituent materials. The results of the nonlinear finite element analyses have been observed to be in good agreement with the experimental, data in terms of failure mechanisms and ultimate load. Failure modes of grouted prisms are also investigated by evaluating the stress distributions at the outer face shell along the prism height. Finally, an analytical relation is proposed to predict the compressive strength of concrete masonry prisms, f(m)(.)(')
Keywords: DAMAGE MODEL; STRENGTH; Construction & Building Technology; Engineering; Materials Science